1990
DOI: 10.1159/000281719
|View full text |Cite
|
Sign up to set email alerts
|

Surface Topography of Deeper Cells Exposed by Ultrasonic Wave Forces in Neoplastic and Non-Neoplastic Epithelium of Human Urinary Bladder

Abstract: The topographic features of deeper cells exposed by ultrasonic wave forces were observed in well-differentiated bladder tumors and in the non-neoplastic bladder mucosa of humans by scanning electron microscopy, and the desquamated cells from these tissues were also observed. The surfaces of these deeper cells and of desquamated cells had two types of cellular protrusions: ‘ripple-like microridges’ and microvillous cellular processes. Slender microvillous cellular processes of various length were observed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Ultrasonography has been utilized for many years to visualize the bladder during fetal development and to estimate bladder volume and identify specific bladder dysfunctions in the adult [Roberts and Rendell, 1989;Fourcroy et al, 1983;Brown et al, 1987;Perkins et al, 1984;Mandell et al, 1992; Suzuki et al, 1990;Abu-Yousef et al, 19841. The current studies demonstrated that ultrasonography is also an easy and quick method of imaging the bladder in rabbits. A person with minimal formal training in ultrasonography technique can be instructed in its use and after sufficient practice can consistently obtain accurate readings on the thickness of the bladder wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonography has been utilized for many years to visualize the bladder during fetal development and to estimate bladder volume and identify specific bladder dysfunctions in the adult [Roberts and Rendell, 1989;Fourcroy et al, 1983;Brown et al, 1987;Perkins et al, 1984;Mandell et al, 1992; Suzuki et al, 1990;Abu-Yousef et al, 19841. The current studies demonstrated that ultrasonography is also an easy and quick method of imaging the bladder in rabbits. A person with minimal formal training in ultrasonography technique can be instructed in its use and after sufficient practice can consistently obtain accurate readings on the thickness of the bladder wall.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography has been utilized in both adult and pediatric urology to visualize the bladder and diagnose conditions such as cancer, postmicturition residual volume, and bladder thickness and function [Roberts and Rendell, 1989;Rabinowitz et al, 1989;Brown eta]., 1987;Mandell et al, 1992;Suzuki et al, 1990;Shapeero et al, 19831. The specific aim of the current study is to develop the use of ultrasonography in conjunction with cystometrograms as a non-surgical measure of the level of bladder hypertrophy present in rabbits, and thus as a measure of the probable functional impairment present.…”
Section: Introductionmentioning
confidence: 99%
“…При этом степень ухудшения крово-тока связана с тяжестью морфологических на-рушений и была наибольшей при лейкоплакии с кератинизацией. Длительно рецидивирующая инфекция мо-чевого пузыря может способствовать формиро-ванию плоскоклеточной метаплазии эпителия слизистой оболочки мочевого пузыря, которую выявляют у 60 % больных хроническим цисти-том [12]. Плоскоклеточную метаплазию можно рассматривать как вариант компенсаторно-при-способительной реакции.…”
Section: результаты и обсуждениеunclassified